2017
DOI: 10.3892/ol.2017.6161
|View full text |Cite
|
Sign up to set email alerts
|

The role of eukaryotic translation initiation factor 6 in tumors

Abstract: Eukaryotic translation initiation factor 6 (eIF6) affects the maturation of 60S ribosomal subunits. Found in yeast and mammalian cells, eIF6 is primarily located in the cytoplasm of mammalian cells. Emerging evidence has demonstrated that the dysregulated expression of eIF6 is important in several types of human cancer, including head and neck carcinoma, colorectal cancer, non-small cell lung cancer and ovarian serous adenocarcinoma. However, the molecular mechanisms by which eIF6 functions during tumor format… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 70 publications
0
16
0
Order By: Relevance
“…eIF6 promotes ATF4 translation and also preferentially activates downstream start-site usage within the CEBPB mRNA, generating the oncogenic LIP isoform [105] ( Figure 4B). Hence upregulation of eIF6 in various types of cancers promotes tumorigenesis [106]. Analogously, it has been proposed that eIF3 on the 40S subunit also has an antijoining function [107] (Figure 5c).…”
Section: Factors With Anti-ribosomal Subunit Joining Activitymentioning
confidence: 67%
“…eIF6 promotes ATF4 translation and also preferentially activates downstream start-site usage within the CEBPB mRNA, generating the oncogenic LIP isoform [105] ( Figure 4B). Hence upregulation of eIF6 in various types of cancers promotes tumorigenesis [106]. Analogously, it has been proposed that eIF3 on the 40S subunit also has an antijoining function [107] (Figure 5c).…”
Section: Factors With Anti-ribosomal Subunit Joining Activitymentioning
confidence: 67%
“…However, nucleolar eIF6 and cytoplasmic eIF6 are required for the biogenesis of 60S subunits and growth factor-stimulated translation, respectively [ 178 ]. Furthermore, an increasing number of studies have demonstrated that there is a highly aberrant expression of eIF6 in various types of human cancer including colorectal cancer, head and neck carcinoma, malignant mesothelioma, acute promyelocytic leukemia and NSCLC (Table 1 ) [ 2 , 179 ]. Therefore, modulation of eIF6 activity or expression may exert an innovative treatment for cancers.…”
Section: Eifs Mis-regulation In Human Cancer and Potential Targets Fomentioning
confidence: 99%
“…EIF6 is potential biomarker for cancer as it downstream modulator of cell division resulting in oncogenesis 54 . ITPA downregulation promotes DNA instability, suppression of cell growth and apoptosis in SKBR3 cell lines 55 .…”
Section: T-sne (T-distributed Stochastic Neighbour Embedding) T-sne mentioning
confidence: 99%